SOME WORDS OLD, SOME WORDS NEW: THE PANDEMIC’S LINGUISTIC FOOTPRINT - Askarova G.X. (PEDAGOGS, 2024)
Abstract. The article discusses the impact that the coronavirus pandemic has had on the vocabulary of the English language. The identified trends include increased frequency in the use of some outdated and specialized vocabulary and the creation of numerous neologisms, mostly by blending.